Application of the Student Teams Achievement Division (STAD) Model to Improve Learning Outcomes in Angle Measurement for Fifth-Grade Students - Maulana Wafi Suhada'; Nur Laili Oktavianti; Vania Nur Khomsah; Dewi Rohmah; Maulida Maulida (Literasi Nusantara, 2026)
Low mathematics learning outcomes in angle measurement at Socah 3 elementary school result from dominant lecture methods and a lack of concrete media. This Classroom Action Research aims to improve grade V students' learning outcomes using a Student Teams Achievement Division (STAD) cooperative model assisted by paper protractors. Initial observations revealed low student involvement and suboptimal conceptual understanding. The results showed significant improvements. In Cycle I, the average score was 78.25 with 14.29% classical completeness, failing due to unfamiliarity with STAD group work. After strengthening peer tutoring and group structures, Cycle II achieved an average of 89.29 and 85.71% completeness, meeting the success indicators. Using paper protractors successfully bridged abstract concepts to concrete understanding. This study highlights shifting teachers into collaborative facilitators and proves that simple, local material-based media impacts learning positively, especially in schools with limited facilities. Future research should test the STAD model broadly using pre-cycle test instruments.